Comprehensive analysis of sesame LRR-RLKs: structure, evolution and dynamic expression profiles under Macrophomina phaseolina stress - Yan, Wenqing; Ni, Yunxia; Zhao, Hui; Liu, Xintao; Jia, Min; Zhao, Xinbei; Li, Yongdong; Miao, Hongmei; Liu, Hongyan; Zhang, Haiyang (Frontiers in Plant Science, 2024)
Leucine-rich repeat receptor-like kinases (LRR-RLKs) can participate in the regulation of plant growth and development, immunity and signal transduction. Sesamum indicum, one of the most important oil crops, has a significant role in promoting human health. In this study, 175 SiLRR-RLK genes were identified in S. indicum, and they were subdivided into 12 subfamilies by phylogenetic analysis. Gene duplication analysis showed that the expansion of the SiLRR-RLK family members in the sesame was mainly due to segmental duplication. Moreover, the gene expansion of subfamilies Ⅳ and Ⅲ contributed to the perception of stimuli under M. phaseolina stress in the sesame. The collinearity analysis with other plant species revealed that the duplication of SiLRR-RLK genes occurred after the differentiation of dicotyledons and monocotyledons. The expression profile analysis and functional annotation of SiLRR-RLK genes indicated that they play a vital role in biotic stress. Furthermore, the protein-protein interaction and coexpression networks suggested that SiLRR-RLKs contributed to sesame resistance to Macrophomina phaseolina by acting alone or as a polymer with other SiLRR-RLKs. In conclusion, the comprehensive analysis of the SiLRR-RLK gene family provided a framework for further functional studies on SiLRR-RLK genes.